2024
DOI: 10.1021/acs.jpcc.3c07221
|View full text |Cite
|
Sign up to set email alerts
|

Ni Drastically Modifies the Microstructure and Electrochemistry of Thin Ti and Cr Layers

Ayesha Kousar,
Ulviyya Quliyeva,
Ishan Pande
et al.

Abstract: There is a significant lack of literature addressing changes in the microstructure of different interfacial metal layer combinations employed in fabricating electrochemical sensors based on carbon nanomaterials. This research gap extends to analyzing their influence on the electrochemical performance, which, in turn, impacts the understanding of the properties of materials incorporating these layers. In this study, microstructural variations and electrochemical activity of chromium and titanium adhesion layers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Moreover, a study on interfacial metal layer combinations demonstrated that Ni decreases the solubility of carbon and oxygen within the Ti-Ni system. As compared to Cr, this allowed the faster formation of segregated ordered carbon, and eventually of an electrochemically active surface layer [51].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a study on interfacial metal layer combinations demonstrated that Ni decreases the solubility of carbon and oxygen within the Ti-Ni system. As compared to Cr, this allowed the faster formation of segregated ordered carbon, and eventually of an electrochemically active surface layer [51].…”
Section: Resultsmentioning
confidence: 99%